Theoretical Analysis of Life Cycle Optimization of Materials Using Artificial Intelligence and Big Data Technologies: Reuse Strategies in the Circular Economy - Silva Aragon, Julio Andres; Manzano Duran, Omaira; Gonzalez Castro, Yolanda (Universidad Francisco de Paula Santander, 2024)
This study emphasizes the revolution represented by the integration of Artificial Intelligence (AI) and Big Data in sustainability and resource efficiency. These technologies improve materials management and foster innovative reuse strategies, essential for the transition to a circular economy. The study uses a qualitative grounded theory approach implementing techniques such as literature review and document analysis.  The results highlight the need for a multidisciplinary approach in the integration of advanced technologies, combining technical skills with a deep understanding of business models and market dynamics, continuous education and training in AI and Big Data, as well as collaboration between companies, educational institutions and government entities are essential to promote innovation and adoption of these technologies in the circular economy.  Finally, we conclude on the importance of integrating advanced technologies in materials management and the need for a holistic approach that combines technological innovations with changes in business models and management practices, emphasizing interdisciplinary collaboration and adaptation to specific contexts to face sustainability challenges.